"Ai, se eu te pego!": um caso de (in)fidelidade - uma leitura holística do hit e suas traduções para o inglês e espanhol à luz da análise crítica do discurso e dos estudos de tradução - Santos, Julio César Ribeiro dos (Universidade Federal de São Carlos, 2019)
We value ourselves from the hit "Ai, si te tego" (TELÓ et al., 2011), viral because of the insertion in multiple discursive practices (FAIRCLOUGH, 2001), and its translations into the English language and the Spanish language for the test of the theoretical-methodological approach of the Translation Studies (LOW, 2003, 2005; VENUTI, 2000; PYM, 2017) and the Critical Discourse Analysis (see Fairclough, 1989, 2001) in the research on the unfolding and problematization of the issues "sense", "fidelity", "domestication / foreignization" (VENUTI, 2000) and "power relations". The research, which has a qualitative nature and ethnographic basis (CRESEWELL, 2010), had 19 informants distributed in three groups and two other informants contacted at different moments of the progress of the research in confrontation / discussion with the researcher's analysis. From the results: a) the translation proposals sin on the questions of naturalness and meaning (see Low, 2005); b) all the informants accuse the same lexical problems; c) the lexical alternatives proposed by native speakers of the foreign languages ​​and speakers of the English and / or Spanish language as L2 disagree; d) the original and the translation proposals are in line with the maintenance of the hegemonic ideology, which is shown in a more crystalline way in the video clip of the proposal for the English language. Although on a rudimentary level, the approximation between discursive studies and translation studies proves to be productive, thus becoming a call for researchers in the field
“Ai, se eu te pego!“: a case of (in)fidelity - a holistic reading of the hit and its translations into english and spanish in light of the and critical discourse analysis and translation studies
Keywords: Análise crítica do discurso; Estudos de tradução; Canção sertaneja; Translation studies; Critical discourse analysis; Sertaneja song; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LINGUISTICA, LETRAS E ARTES; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA